New Hard Boiled Candy Development by Incorporation of D. kaki Leave Extract to Reduce Migraine Headache - Rubab, Ruqayya; Mujahid, Maryam; Rehmani, Midhat; Khan, Shanzay (Journal of Research (Science), 2025)
Product development is the life-blood of companies and societies. In the present study a new migraine headache reducing candy was produced by incorporating of a fruit plant persimmon i.e. D. kaki. Among the various combinations, the D. kaki mixed candy containing 80mg/5g was found better than other combinations in respect to organoleptic properties and nutritional quality. The addition of 80mg/5gm of D. kaki to produce candy imparts migraine reducing impact. The pH, energy contents, moisture, ash, total soluble solids, titrable acidity, protein, fiber, and carbohydrate of newly developed anti-aging toffee were found to be 6.7±0.01, 47.14±1.9 kcal/5g, 7.9±0.05%, 2.82±0.02%, 62.7± 1.2%, 0.17± 0.02%, 1.95 ± 0.03%, 0.75 ± 0.01% and 54.5 ± 0.94% respectively. The standard plate counts were found to be less than the detection limit. On the sensory and microbiological point of view, the presently developed candy was found highly acceptable. The total aerobic plate count and mold count were found to be the acceptable according to food standards. The newly established candy imparts anti-migraine impact due to medicinal importance of the ingredients. There is several confectionery products sold in the market and are happily consumed by the consumers and few of them have medicinal properties, but no hard boiled candy with migraine headache reducing properties have been reported in the literature earlier. Therefore, the introduction of this first ever candy as remedy of migraine headache in the market will improve the health of consumers as well as the product cycle of the industry. It also has the market competent price therefore the product is likely to gain the attraction of consumer and improves the market trends.